The Preparedness of Hospital Emergency Departments for Responding to Disasters in Iran; a Systematic Review and Meta-Analysis - Mosayeb Kazemzadeh (Archives of Academic Emergency Medicine, 2019)
Introduction: Hospitals are the most important infrastructures of any society. The hospital emergency department is one of the most important wards of hospitals in response to disasters. The purpose of this study was to evaluate the preparedness of hospital emergency departments in response to disasters in Iran via a systematic review and meta-analysis.